Prolonged starvation deepens quiescence in Vasa2/Piwi1-expressing cells of a sea anemone - Pascual-Carreras, Eudald; Garschall, Kathrin; Steinmetz, Patrick R. H. (PLOS Biology, 2025)
Animals with lifelong growth adjust their growth rates to nutrient availability, yet the underlying cellular and molecular mechanisms remain poorly understood. Here, we studied how food supply and TOR signaling regulate the cell cycle in a multipotent population of Vasa2-/Piwi1-expressing cells in the sea anemone Nematostella vectensis. We discovered that starvation induces a reversible G1/G0 cell cycle arrest in Vasa2+/Piwi1+ cells and that cell cycle re-entry upon refeeding is dependent on TOR signaling. In addition, the length of the refeeding stimulus after starvation determines the proportion of cells that re-enter S-phase. Remarkably, prolonged starvation delayed both refeeding-induced TOR signaling activation and S-phase re-entry, and led to a global decrease in the active histone mark H3K27ac in Vasa2+/Piwi1+ cells. This strongly suggests that Nematostella Vasa2+/Piwi1+ cells undergo starvation-controlled quiescence deepening, a phenomenon previously described only in unicellular eukaryotes and mammalian cell culture. The nutritional control of quiescence and cell proliferation may thus be a fundamental, evolutionarily conserved strategy underlying the environmental regulation of indeterminate growth in animals.